The potential trade‐off between artisanal fisheries production and hydroelectricity generation on the Kafue River, Zambia. (18th January 2013) - DEINES, ANDREW M.; ADAM BEE, C.; Katongo, Cyprian; JENSEN, RICHARD; LODGE, DAVID M.
Summary 1. Freshwater resource managers are increasingly obligated to consider the impacts of large river engineering projects on ecosystem services. We evaluated the effect of altered water regime from the operation of a large dam on the production of the downstream tropical floodplain fishery of the Kafue River, Zambia. We compared the benefits of increased hydropower relative to potentially lost fishery production. 2. We compiled a long‐term data set consisting of experimental gillnet catches, artisanal harvesting effort and monthly river flows for 25 years prior to and 29 years after the 1977 completion of the upstream Itezhi‐Tezhi Dam. As a metric of the flood regime, we calculated a canonical correlation score for each hydrological year before and after dam closure. For the period following dam construction, we used the Muskingum method of flood routing to estimate 'no‐dam' flows through the fishery area and downstream hydroelectric turbines at the Kafue Gorge Dam. 3. We compared 16 alternative models of catch per unit effort (CPUE) with and without an effect of water regime on fish population growth rate. Using the two best fitting models, we estimated the total observed fishery harvest and simulated 'no‐dam' fisheries harvest and found no significant effect of altered water regime on fishery production. 4. We estimate that the large upstream dam increases downstream hydropower production by about 18 million USD per annum. The reduction in fishery production caused by the altered water regime is not significantly different than zero, although the average reduction amounts to about 2.3 million annually. The total estimated value of harvest ranges from 1.3 million to 56 million annually. 5. Large observed declines in fish abundance over the 54‐year study period are attributed primarily with similarly large increases in total fishing effort in this mostly open‐access artisanal fishery. 6. These results contrast with other examples of the effects of flow alteration on fish, probably because levels of fisheries exploitation on the Kafue River are very high relative to better studied regions on other continents; our focus on the whole fish community; and the unprecedented length of the time series we considered. If the goal is to sustain fishery production, investments in altering flow regime are likely to be less effective than investments to decrease fishing effort.